2009
DOI: 10.1016/j.visres.2009.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser induced flexibility change of human donor lenses

Abstract: The creation of gliding planes with a fs laser inside the crystalline lens tissue can change the deformation ability of the lens. This might be an indication for a possible method to treat presbyopia in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
0
32
0
1
Order By: Relevance
“…9,10 A similar strategy is applied in the concept of fs-laser presbyopia treatment, which aims to restore the elasticity of the lens by inducing laser disruptions in the hardened lens nucleus. [11][12][13] Moreover, fs-laser-induced cuts within the vitreous body may reduce vitreous traction and are therefore discussed as a preventive therapy for posterior vitreous detachment.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 A similar strategy is applied in the concept of fs-laser presbyopia treatment, which aims to restore the elasticity of the lens by inducing laser disruptions in the hardened lens nucleus. [11][12][13] Moreover, fs-laser-induced cuts within the vitreous body may reduce vitreous traction and are therefore discussed as a preventive therapy for posterior vitreous detachment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the flexibility of the lens increased depending on the particular cutting pattern [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The first experimental results were promising. [6][7][8] Studies show that the procedure can be applied successfully in porcine, 8 human cadaver donor, 9 and rabbit 10 eyes. The laser microincisions inside the crystalline lens were detectable on OCT and Scheimpflug imaging, which emphasizes the integral role these technologies play in targeting and characterizing postoperative tissue effects.…”
Section: Discussionmentioning
confidence: 99%
“…8 The microincisions inside the lens tissue are created with femtosecond laser pulses in a manner similar to flap generation in laser in situ keratomileusis. 8 The first in vitro studies of porcine 8 and human 9 donor lenses showed increased lens deformability after treatment.…”
mentioning
confidence: 99%